Assessing Three-Dimensional Art Objects Quantitative Evaluation of Qualitative Achievements in Art and Design Education - Nedina Sari (ITB Journal Publisher, LPPM ITB, 2013)
Knowledge about shaping three-dimensional objects is tangibly and conceptually relevant to human activities within a spatial environment, and is part of formal arts and design education as one of the basic elements in the process of learning about creating functional artifacts and art objects. Basic skills connected with this knowledge are conveyed in 'Basic Three-Dimensional Object' class, which is aimed at conveying a deeper understanding of three-dimensional objects as touchable and visible, and occupying a structural space. Learning this entails is quite an elaborate exploration, which, when evaluated afterward, is of a qualitative nature. However, in higher education every step of the learning process is quantified in order to validate the students' achievements. This requires an objective judgment from the lecturer, despite the fact that many parameters which are relevant for art objects are not exact. Therefore, once grades are released, not all students understand the meaning of numbers that represent their grades. These numbers are of a precise, quantitative nature, while explanations from lecturers in non-exact narrations are of a qualitative nature. The contrast between these two types of evaluation has raised questions such as: is quantitative grading an appropriate method, or is it better to use a subjective validation to appreciate creativity?